MODIFIKASIZEOLIT ALAM MORDENIT SEBAGAI KATALISATOR KETALISASI DAN ESTERIFIKASI - Nuryoto Nuryoto; Hary Sulistyo; Wahyudi Budi Sediawan; Indra Perdana (Dept. of Chemical Engineering, Diponegoro University, 2016)
Abstract MODIFIED MORDENITE NATURAL ZEOLITE AS CATALYST FOR KETALIZATION AND ESTERIFICATION. The aims of this research was studied of modified mordenite natural zeolite from Bayah effect by acidity and heating to change zeolite characteristics in orde to prepare as catalyst for glycerol ketalization and acetit acid esterification by some reaction temperature variation. Natural zeolite which modified by precise treatment will be produced of natural zeolite that ready for use as catalyst and has good perfomance. The characterization results showed that the best condition for modified mordenite natural zeolite of Bayah achieved at sulfuric acid concentration of 6 N and heating temperature of 200oC, by surface area reached of 157.110 m2/g and cation exchanged capacity of 2.11 meq/ml. Modernite natural zeolite of Bayah has good performance indication as a catalyst, by the highest glycerol conversion of 70.10% at 60°C for the ketalization reaction, and for the esterification reaction, mordenit natural zeolit of Bayah able to acetit acid conversion of 11.72% at 70°C. Keywords: characterization; esterification; glycerol; modified; ketalization Abstrak Penelitian ini bertujuan untuk untuk mempelajari pengaruh modifikasi dengan pengasaman dan pemanasan terhadap perubahan karakteristik zeolit alam mordenit dari Bayah guna persiapan sebagai katalisator pada reaksi ketalisasi gliserol dan esterifikasi asam asetat dengan beberapa variasi suhu reaksi. Zeolit alam yang termodifikasi dengan perlakuan yang tepat akan menghasilkan zeolit alam yang siap pakai, dan akan mampu menghasilkan performa yang baik. Hasil pengujian karakterisasi menunjukkan bahwa kondisi terbaik pada modifikasi zeolit alam mordenit Bayah dihasilkan pada konsentrasi pengasaman 6N H2SO4 dan suhu pengeringan 200oC dengan luas permukaan 157,110 m2/g dan kemampuan tukar kation sebesar 2,11 meq/ml. Zeolit alam mordenit Bayah menunjukkan performa yang baik sebagai katalisator dengan konversi gliserol tertinggi sebesar 70,10% yang dicapai pada suhu 60oC pada reaksi ketalisasi, dan untuk reaksi esterifikasi, zeolit alam mordenit Bayah mampu mengkonversi asam setat sebesar 11,72% pada suhu 70oC. Kata kunci: karakterisasi; esterifikasi; gliserol; modifikasi; ketalisasi